KONSELING BEHAVIOR DENGAN TEKNIK PENGUATAN POSITIF UNTUK MENINGKATKAN KEAKTIFAN BERTANYA PADA MATA PELAJARAN BAHASA JAWA - Salsabila, Putri; Hidayati, Richma; Sucipto, Sucipto (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The objectives of this research are: (1) To find the factors causing the lack of active questioning in students Javanese language learning for SMP I Pesantren Nurul Ishlah Al-Anwar. (2) Help increase the activity of asking students through a behavior approach with techniques reinforcement positive for students at SMP I Pesantren Nurul Ishlah Al-Anwar. Behavior approach is a counseling process carried out by the counselor to the counselee using a behavioral approach and certain techniques in solving the problems encountered. Positive reinforcement techniques are techniques that strengthen counselees to achieve appropriate behavior changes by providing rewards in the form of support, praise, attention, sympathy, empathy. The research used by the researcher is a qualitative descriptive case study. The subjects studied were two class VIII students, namely KA and NLM, these students experienced low activity in asking questions in Javanese language subjects. The researcher used observation and interview data collection methods. From the research results, it is proven that behavioral counseling using positive reinforcement techniques can increase the activeness of asking questions in Javanese language, increase enthusiasm for learning, independent learning activities for students of SMP I Pesantren Nurul Ishlah Al-Anwar. The application of the behavioral counseling approach with positive reinforcement techniques overall solved the problems experienced by the two counselees. This was obtained through the researcher's observations in the counseling process, which initially showed a passive attitude to ask questions, now they are actively asking questions and are eager to learn.